Personalised BEEF shooting training for female basketball players: Enhancing accuracy and consistency - Bayu, Wahyu Indra; Solahuddin, Soleh; Mohamad, Nur Ikhwan; Nanda, Fitri Agung; Yusfi, Herri (UIR Press, 2025)
Background: Shooting accuracy is critical for basketball players to be able to score as many points as possible and outperform opponents. While it is critical to have the ability to score, female players in Palembang City tended to preserve their incorrect shooting form, which led to the inconsistency of their shooting accuracy. Research Objectives: This study aims to analyse the comparison between the effect of personalised and group repetition training on shooting accuracy and consistency for female basketball players. Methods: This study uses a pretest-posttest control group design, using SPSS v26 to generate the tabulation and statistical analysis. A total of 30 female basketball players aged 17-21 (19.14±1.18) were selected as the research sample. Participants were divided into two groups using ordinal pairing based on the results of the pretest from various competitive levels and participated in a 12-week training program tailored to their shooting mechanics and performance metrics. Finding and Results: Results indicated that the experimental group significantly improved shooting accuracy and consistency compared to the control group. The personalised training approach addressed individual biomechanical flaws and optimised shooting techniques, enhancing performance, which was shown in the average value of the experiment group that was higher than the control group. Additionally, players reported gaining more confidence and motivation due to the tailored nature of the training. Conclusion: This study highlights the potential of personalised training programmes in sports, emphasising the need for individualised approaches to optimise athlete performance. Further research is recommended to explore long-term effects and applicability across different sports skills and levels.